Developing rules and criteria for rice ontology construction. (2nd June 2009) - Thunkijjanukij, Aree; Kawtrakul, Asanee; Panichsakpatana, Supamard; Veesommai, Uamporn
The Rice Production Ontology (RPO) was constructed from scratch in consultation with domain-experts. This ontology covers the domain of rice production from cultivation to harvesting. Refinement in the loop was done by performing the transformation following the criteria validated by expert to improve the created ontology. The RPO contains 2322 concepts and 5603 terms in a system of hierarchical and 57 associative relations and provides an organisational framework that allows reasoning about rice production knowledge. From the study, eight criteria for constructing ontology and five rules for the semi-automatic maintenance were derived.